PEMODELAN SISTEM RESAPAN AIR HUJAN DAN LIMBAH AIR WUDHU DI AREA MASJID - Radius Pranoto; Andrijanto; Debby Rahmawati (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2019)
As already known, one alternative to solve run-off problem is by recharging the water into soil by mean of adiffusion system. This way can be expected to be able to conserve ground water. This research was aimed to model a diffusion system conserving rainfall runoff and ablution waste from the mosque of Al-Wasi'i of Lampung University. This research was conducted from July to September 2011. Experiment data used in the modeling consisted of a week daily ablution waste discharged from the mosque, percolation rate, surface evaporation. The ablution waste data was collected both on and off semesters. Percolation rates of three location sites aroung the mosque were measured by using double ring infiltrometer. Surface evaporations were measured by contructing a 30x30x45 cm glass container simulating a runoff collector. The actual evaporation was then used to calibrate the constant (K) by comparing with the Penmann reference evapotranspiration (ETo). The contant was then validated by another group of actual evaporation data. In addition to the experimental data, a 10 year daily climotological data was also used and collected from the nearest weather station. The model consisted of input conponents: praying ablution wsate, runoff from the mosque’s roof, direct rainfall, and output components: overflow, evaporation, and percolation. The model simulated daily up and down water surface of the diffusion system. The result showed that there were three different percolation rates from three diferent locations, but the stable rate of 1666.12 mm/day was more likely representative and used in this model. Based on the simulation, diffusion system of 3 m depth and 8 m2 area could conserve the water by 70%.